Boron‐ versus Nitrogen‐Centered Nucleophilic Reactivity of (Cyano)hydroboryl Anions: Synthesis of Cyano(hydro)organoboranes and 2‐Aza‐1, 4‐diborabutatrienes. Issue 37 (26th May 2021) - Gärtner, Annalena; Marek, Matthäus; Arrowsmith, Merle; Auerhammer, Dominic; Radacki, Krzysztof; Prieschl, Dominic; Dewhurst, Rian D.; Braunschweig, Holger
Abstract: Cyclic alkyl(amino)carbene‐stabilized (cyano)hydroboryl anions were synthesized by deprotonation of (cyano)dihydroborane precursors. While they display boron‐centered nucleophilic reactivity towards organohalides, generating fully unsymmetrically substituted cyano(hydro)organoboranes, they show cyano‐nitrogen‐centered nucleophilic reactivity towards haloboranes, resulting in the formation of hitherto unknown linear 2‐aza‐1, 4‐diborabutatrienes. Abstract : Cyclic alkyl(amino)carbene‐stabilized (cyano)hydroboryl anions were synthesized by deprotonation of the corresponding (cyano)dihydroborane precursors. They display boron‐centered nucleophilic reactivity towards organohalides but cyano‐nitrogen‐centered nucleophilic reactivity towards haloboranes, resulting in the formation of the first linear 2‐aza‐1, 4‐diborabutatrienes.